Efektivitas Pengelolaan Alokasi Dana Gerdema dan RT Bersih di Desa Taras, Kecamatan Malinau Barat, Kabupaten Malinau - Cledwin, Dede; Darmanto, Darmanto; Daryono, Daryono (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
There are several village fund budget realisations that have not been optimal and have not met development targets. This study examines the efficiency of managing the allocation of the Regional Budget (APBD) through the Gerdema (Gerakan Desa Membangun) and RT BERSIH (Rapi, Tertibib, Bersih, Sehat, Indah, dan Harmonis) programmes in Taras Village. Qualitative data analysis in this study uses the theory of effectiveness and the ratio of effectiveness criteria. The findings of this study reveal that the management of Gerdema and RT BERSIH funds in Taras Village is in the effective category. Challenges faced in the implementation of fund management include limited community understanding of budget utilisation, communication barriers, and delays in fund disbursement. To overcome these obstacles, it is recommended to conduct training sessions, improve coordination between work units, and provide assistance.